Hubungan intensitas penggunaan media sosial dengan kualitas tidur pada remaja - Anggraeni, Ratisa Dwipa; Suryani, Suryani; Sudyasih, Tiwi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Adolescence is a period marked by physical and psychological changes that can affect sleep patterns. Sleep is essential for adolescents because it plays a role in maintaining physical condition and readiness to carry out daily activities. Lack of quality and duration can lead to less than optimal body conditions, such as the risk of hypertension due to autonomic nervous system disorders, increased inflammation, and changes in metabolism and body weight. Other impacts include fatigue, lethargy, difficulty concentrating, anxiety, headaches, and excessive sleepiness. Purpose: To determine the relationship between the intensity of social media use and sleep quality in adolescents. Method: This non-experimental quantitative research used a cross-sectional study approach. The population of this study was 105 students in grades 10 and 11. The sampling technique used total sampling. The instrument used to measure sleep quality was the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while the Social Media Use Intensity questionnaire was used to measure the intensity of social media use. Data analysis used the non-parametric Spearman Rho test. Results: The results of statistical tests using the Spearman Rho test show a significant relationship between sleep quality and intensity of social media use with values ​​(p = 0.005) and (r = 0.274) indicating a positive relationship with a low level of closeness. Conclusion: There is a significant relationship and a weak relationship between sleep quality and the intensity of social media use in grade X and XI.   Keywords: Adolescents; Intensity Of Social Media Use; PSQI; Sleep Quality.   Pendahuluan: Masa remaja adalah periode yang ditandai dengan perubahan fisik dan psikologis yang dapat memengaruhi pola tidur. Tidur sangat penting bagi remaja karena berperan dalam menjaga kondisi fisik dan kesiapan untuk melakukan aktivitas sehari-hari. Kurangnya kualitas dan durasi tidur dapat menyebabkan kondisi tubuh yang kurang optimal, seperti risiko hipertensi akibat gangguan sistem saraf otonom, peningkatan peradangan, dan perubahan metabolisme serta berat badan. Tujuan: Untuk mengetahui hubungan antara intensitas penggunaan media sosial dan kualitas tidur pada remaja. Metode: Penelitian kuantitatif non-eksperimental ini menggunakan pendekatan studi cross-sectional. Populasi penelitian ini adalah 105 siswa kelas 10 dan 11. Teknik pengambilan sampel menggunakan total sampling. Instrumen yang digunakan untuk mengukur kualitas tidur adalah kuesioner Pittsburgh Sleep Quality Index (PSQI), sedangkan kuesioner Intensitas Penggunaan Media Sosial digunakan untuk mengukur intensitas penggunaan media sosial. Analisis data menggunakan uji Spearman Rho non-parametrik. Hasil: Hasil uji statistik menggunakan uji Spearman Rho menunjukkan hubungan yang signifikan antara kualitas tidur dan intensitas penggunaan media sosial dengan nilai (p = 0,005) dan (r = 0,274) yang menunjukkan hubungan positif dengan tingkat kedekatan yang rendah. Simpulan: Terdapat hubungan yang signifikan dan hubungan yang lemah antara kualitas tidur dan intensitas penggunaan media sosial pada siswa kelas X dan XI.   Kata Kunci: Intensitas Penggunaan Media Sosial; Kualitas Tidur; PSQI; Remaja.